2021
DOI: 10.1002/tesq.3090
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Supports for Language Development through English‐Medium Instruction: A Factor Analysis

Abstract: The purpose of this paper is to build and test a framework of four factors stakeholders in postgraduate higher education institutions in Kazakhstan perceive as supporting or hindering language development in English‐medium programs. Data in this mixed‐methods study were collected through student surveys and interviews with students, faculty and administration from six universities across Kazakhstan. Factor analysis confirmed the value of structural, pedagogical, sociolinguistic, and cultural factors for langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Interestingly, EMI research in Kazakhstani downplays professors' linguistic adaptation as "pedagogical habitus engagement" and how their "embodied cognitive and corporeal habitus" increases or devalues their capitals (Fataar & Feldman, 2017, p. 188); they merely point to the factors that influence EMI teaching and the effectiveness of approaches and methods in language education and pedagogy. For example, Goodman et al (2022) found structural, pedagogical, sociolinguistic, and cultural factors that need to be considered when implementing EMI interventions, while Satayev et al (2022) emphasised the crucial role of content and languageintegrated learning (CLIL). Polatova et al ( 2020) investigated the effectiveness of digital tools and mobile applications in improving students' communicative competence in business English courses.…”
Section: Taking Stock Of the Kazakhstani Higher Education (He) Fieldmentioning
confidence: 99%
“…Interestingly, EMI research in Kazakhstani downplays professors' linguistic adaptation as "pedagogical habitus engagement" and how their "embodied cognitive and corporeal habitus" increases or devalues their capitals (Fataar & Feldman, 2017, p. 188); they merely point to the factors that influence EMI teaching and the effectiveness of approaches and methods in language education and pedagogy. For example, Goodman et al (2022) found structural, pedagogical, sociolinguistic, and cultural factors that need to be considered when implementing EMI interventions, while Satayev et al (2022) emphasised the crucial role of content and languageintegrated learning (CLIL). Polatova et al ( 2020) investigated the effectiveness of digital tools and mobile applications in improving students' communicative competence in business English courses.…”
Section: Taking Stock Of the Kazakhstani Higher Education (He) Fieldmentioning
confidence: 99%
“…In recent decades, scholars have extensively explored the different dimensions of EMI programs. These include (1) language policy and planning (Karabassova, 2021; Kerimkulova et al ., 2023; Sah and Fang, 2023; Goodman and Karabassova, 2018), (2) teaching and learning processes (Goodman et al ., 2023; Richards and Pun, 2022), (3) perceptions of different stakeholders towards EMI (Al-Riyami and Dayananda, 2022; Goodman et al ., 2022), (4) challenges and concerns (Hajar and Mhamed, 2021; Hajar et al ., 2023; Pun et al ., 2023; Sarmurzin et al ., 2023), (5) teachers' perspectives and training (Deroey, 2023; Macaro and Han, 2020; Karabassova, 2018), (6) student motivation and attitudes (Kojima, 2021; Turhan and Kirkgöz, 2018), (7) discourse of emotions (Hillman, 2023; Sah, 2023a, b; Yuan et al ., 2023), and so on. Initial research conducted in regions such as Hong Kong, where English has been the primary medium of instruction for a considerable period, indicated predominantly favorable perceptions towards EMI, as reported by Evans and Morrison (2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers are conducting a comparative experimental study based on the above example. The following are the methods used to plan, collect data, and evaluate the implementation of the survey (Aitzhanova et al, 2022). The study is divided into six phases, including pre-experimental grouping, pre-experimental testing, study implementation, post-experimental testing, questionnaires and interviews, data processing, and analysis of results.…”
Section: Experimental Designmentioning
confidence: 99%